Attaining the Sustainable Development Goals in Africa: The New Corporate Social Responsibility for Multinational Corporations - Amodu, Nojeem (Journal of Sustainable Development Law and Policy, 2025)
The fact that Africa is one of the worst performing regions in global audits about long-term development trends is longer news. The continent has repeatedly missed targets set by the United Nations and there are concerns it might just be left behind in the attainment of the latest 2030 Agenda Sustainable Development set by world leaders in 2015. With a view to complementing states’ responsibilities towards the provision of public goods and social services useful to actualize the Sustainable Development Goals (SDGs) in Africa, this article interrogates the nature of multinational corporations (MNCs) and juxtaposing the non-state actor responsibilities within wider societal contexts with state duties in advancing the SDGs. The article not only sets the tone for a “new corporate social responsibility” in terms of improved pursuit of sustainability within business communities in corporate Africa, it also recommends workable measures, integrating progressive roles for both the state and MNCs towards the realization of the SDGs on the continent.